2020
DOI: 10.1002/jmri.27212
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Amide Proton Transfer MRI and Diffusion‐Weighted Imaging in Assessing p53 and Ki‐67 Expression of Rectal Adenocarcinoma

Abstract: Background The evaluation of prognostic factors in rectal carcinoma patients has important clinical significance. P53 status and the Ki‐67 index have served as prognostic factors in rectal carcinoma. Amide proton transfer (APT) imaging has shown great potential in tumor diagnosis. However, few studies reported the value of APT imaging in evaluating p53 and Ki‐67 status of rectal carcinoma. Purpose To investigate the feasibility of amide proton transfer MRI in assessing p53 and Ki‐67 expression of rectal adenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
3
21
1
Order By: Relevance
“…Second, Ki-67 LI was calculated as the mean positive cell count in the cellular area, and it therefore could not be directly compared with the mean APT SI value, which was calculated from the ROI covering the whole tumor including necrosis. Although several previous studies have reported positive correlations between APT SI and Ki-67 LI in gliomas 29 , meningiomas 30 , and rectal carcinomas 31 , no correlation was found in rectal adenocarcinomas 51 . There have been few studies on the utility of APT imaging in the differential diagnosis of different breast tumors 26,28 , and further investigation will be required to determine whether there is an association between APT SI and Ki-67 LI.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Second, Ki-67 LI was calculated as the mean positive cell count in the cellular area, and it therefore could not be directly compared with the mean APT SI value, which was calculated from the ROI covering the whole tumor including necrosis. Although several previous studies have reported positive correlations between APT SI and Ki-67 LI in gliomas 29 , meningiomas 30 , and rectal carcinomas 31 , no correlation was found in rectal adenocarcinomas 51 . There have been few studies on the utility of APT imaging in the differential diagnosis of different breast tumors 26,28 , and further investigation will be required to determine whether there is an association between APT SI and Ki-67 LI.…”
Section: Discussionmentioning
confidence: 72%
“…We found that the combined ADC change using different T d values had a signi cant positive correlation with APT SI. Previous studies have reported that time-dependent DWI or CEST imaging might provide information about tumor microstructure indicating tumor proliferation in oncologic imaging [28][29][30][31][32] . Comparisons of APT SI and IVIM parameters in cervical cancers 33 , gliomas 34 , and hepatocellular carcinomas 35 , as well as comparisons of APT SI and diffusion kurtosis imaging in rectal carcinomas 36 , have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile proteins and peptides are thought to have a close relationship with tumor growth activity. The clinical utility of APT imaging has already been demonstrated in glioma, lung cancer, prostate cancer, and rectal cancers [15][16][17][18]. In gynecology, APT signals have demonstrated a correlation with the histologic grades of endometrioid endometrial carcinoma [19] and the efficacy in differentiating cervical cancer from normal cervical tissue [20].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of JMRI, the article by Li et al 10 fits into this scenario, and advances our understanding of rectal cancer by exploiting the application of APT MRI for the detection of diagnostic and prognostic noninvasive MRI markers. In this well‐designed study the authors found significantly higher APT signal intensity in high‐grade tumors, more advanced‐stage tumors, and in tumors with lymph node metastases.…”
mentioning
confidence: 99%